Effectiveness of the drills & practice method on improving skills of reading basic notation among 4 sedeli students at Sekolah Kebangsaan Taman Sri Andalas, Klang / Norhayati A. Kadir - A. Kadir, Norhayati (2016)
Music is one of the art elements that should be taught and guided so it is suitable with the community culture. Effective delivery of teaching and learning will lead to students success. The purpose of this study is to examine the relationship between the respondents' learning achievement in recognizing basic music notations and symbols with the use of Drills & Practice Method . The study also sought to test the effectiveness of the above methods on the students' interest in the subject itself. The study was conducted at Sekolah Kebangsaan Taman Sri Andalas, Klang Selangor, which involved 25 students' from Year 4 Sedeli Class as the respondents. The research instruments are questionnaires, tests, flash cards and feedback checklist. In general, the findings show the effectiveness of the Drills & Practice Method in teaching basic music notations and symbols in music theory. The results from the study support the aim of using Drills & Practice Method in the teaching and learning session of basic music to Year 4. In addition, it is expected to be developed as an alternative for teachers to be used as teaching and learning methods in the classroom.